Prevention of Fab-arm exchange and antibody reduction via stabilization of the IgG4 hinge region. Issue 1 (1st January 2020) - Handlogten, Michael W.; Peng, Li; Christian, Elizabeth A.; Xu, Weichen; Lin, Shihua; Venkat, Raghavan; Dall'Acqua, William; Ahuja, Sanjeev
ABSTRACT: IgG4s are dynamic molecules that undergo a process called Fab-arm exchange. Disulfide bonds between heavy chains are transiently reduced, resulting in half antibodies that reform intact antibodies with other IgG4 half antibodies. In vivo, therapeutic IgG4s can recombine with endogenous IgG4s, resulting in a heterogeneous mixture of bispecific antibodies. A related issue that can occur for any therapeutic protein during manufacturing is interchain disulfide bond reduction. For IgG4s, this primarily results in high levels of half-mAb that persist through purification processes. The S228P mutation has been used to prevent half-mAb formation. However, we demonstrated that IgG4s with the S228P mutation are subject to half-mAb formation and Fab-arm exchange in reducing environments. We identified two novel mutations that stabilize the heavy–heavy chain interaction via incorporation of additional disulfide bonds in the hinge region. Individually, these mutations increase stability toward reduction and lessen Fab-arm exchange. Combination of all three mutations, Y219C, G220C, and S228P, has an additive benefit resulting in an IgG4 with ˃7-fold increase in stability toward reduction while preventing Fab-arm exchange. Importantly, the mutations do not affect antigen binding or Fc effector function. These mutations hold great promise for solving mAb reduction during manufacturing and preventing Fab-arm exchange in vivo.